Reproducible experiments on dynamic resource allocation in cloud data centers. (July 2016) - Wolke, Andreas; Bichler, Martin; Chirigati, Fernando; Steeves, Victoria
Abstract: In Wolke et al.[1] we compare the efficiency of different resource allocation strategies experimentally. We focused on dynamic environments where virtual machines need to be allocated and deallocated to servers over time. In this companion paper, we describe the simulation framework and how to run simulations to replicate experiments or run new experiments within the framework. Abstract : Highlights: Simulation and experimentation framework that allows an extensive evaluation of VM allocation strategies. Supports initial VM allocation controllers and dynamic controllers with VM migrations and random VM arrivals/departures. More than 200 time series data sets describing workload in enterprise data centers. The software framework allows for the design of new experiments and the replication of those published in Wolke et al.[1] .